Voltage distribution in the windings of high temperature inverter-fed motors. Issue 5 (3rd September 2018) - Roger, Daniel; Napieralska-Juszczak, Ewa
Abstract : Purpose: High-temperature (HT°) motors are made with inorganic coils wound with a ceramic-coated wire. They must be carefully designed because the HT° insulating materials have a lower breakdown voltages than the polymers used for insulating standard machines. Design/methodology/approach: The voltage distribution between stator coils is computed with high-frequency (HF) equivalent circuits that consider the magnetic couplings and the stray capacitances. Two time scales are used for getting a fast computation of very short voltage spikes. For the first step, a medium time scale analysis is performed considering a simplified equivalent circuit made without any stray capacitance but with the full PWM pattern and the magnetic couplings. For the second step, a more detailed HF equivalent circuit computes voltage spikes during short critical time windows. Findings: The computation made during the first step provides the critical time windows and the initial values of the state variables to the second one. The rise and fall time of the electronic switches have a minor influence on the maximum voltage stress. Conversely, the connection cable length and the common-mode capacitances have a large influence. Research limitations/implications: HF equivalent circuits cannot be used with random windings but only to formed coils that have a deterministic position of turns. Practical implications: The proposed method can be used designing of HT° machine windings fed by PWM inverter and for improving the coils of standard machine used in aircraft's low-pressure environments. Originality/value: The influence of grounding system of the DC link is considered for computing the voltage spikes in the motor windings.